Community Management of Acute Malnutrition (CMAM) in Odisha, India: A Multi-Stakeholder Perspective - Sanghamitra Pati; Sandeep Mahapatra; Rajeshwari Sinha; Sandipana Pati; Satya N. Samal (Frontiers Media S.A., 2018)
India remains home to nearly one-third of the world's children with severe and acute malnutrition (SAM). The present study looks at the function and implementation of a Community Management of Severe Acute Malnutrition (CMAM) programme for treatment of children with SAM in Odisha, an Indian state. A cross-sectional study design using qualitative techniques with direct observation of process and infrastructure was adopted to explore the views of stakeholders on the programme implementation. The study focuses on Kandhamal, a district in Odisha, and was conducted during June-August, 2015. Of the district and community level stakeholders involved in CMAM programme, 49 were selected as study participants using purposive sampling. In-depth interviews were conducted to obtain relevant information. Data was analyzed using data analysis software, atlas.ti version 7. The analysis demonstrated the overall acceptability, feasibility and economic viability of the programme. Additionally, the study identified several enablers (such as good response from child, village leadership involvement, multisectoral participation etc.) and barriers (such as limited awareness, increased work load, irregular staff payment etc.) linked to programme implementation. Interactions with beneficiaries and stakeholders also provided the real picture on the ground. The study emphasizes the need for stakeholders to work responsibly and in unison, and need for beneficiaries to accept, participate and contribute to the programme. In view of maximum impact, the study recommends that CMAM programmes be implemented with existing primary healthcare facilities. The study also outlines future scope for policy-level interventions and support to ensure sustainability of this healthcare delivery model.